Accidental Dural Puncture and Postdural Puncture Headache: What Are Our Options?. Issue 1 (March 2017) - Van de Velde, M.
Abstract : ( Reg Anesth Pain Med. 2016;41(2):121–122) Accidental dural puncture (ADP) and consequent postdural puncture headache (PDPH) in obstetric patients are a cause for concern as the latter is associated with mortality and morbidity.